2017
DOI: 10.3390/genes8070174
|View full text |Cite
|
Sign up to set email alerts
|

MYC Modulation around the CDK2/p27/SKP2 Axis

Abstract: MYC is a pleiotropic transcription factor that controls a number of fundamental cellular processes required for the proliferation and survival of normal and malignant cells, including the cell cycle. MYC interacts with several central cell cycle regulators that control the balance between cell cycle progression and temporary or permanent cell cycle arrest (cellular senescence). Among these are the cyclin E/A/cyclin-dependent kinase 2 (CDK2) complexes, the CDK inhibitor p27KIP1 (p27) and the E3 ubiquitin ligase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 267 publications
(458 reference statements)
5
59
0
Order By: Relevance
“…18,43 Accordingly, c-MYC, SKP2, and p27 have been proposed to form a network, and reducing the activity of c-MYC and SKP2 or boosting nuclear p27 expression is explored as a therapeutic strategy. 45 Since p27 was increased at only protein levels but not at mRNA levels after knockdown of FACT in our present study, our data support the notion that FACT exerts its influence on p27 at post-transcriptional levels. The reduction in both mRNA and protein levels of SKP2 and c-MYC with knockdown of FACT and an enrichment of FACT binding at c-MYC promoter region indicate that FACT enhances the transcription of c-MYC in prostate and lung cancer cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…18,43 Accordingly, c-MYC, SKP2, and p27 have been proposed to form a network, and reducing the activity of c-MYC and SKP2 or boosting nuclear p27 expression is explored as a therapeutic strategy. 45 Since p27 was increased at only protein levels but not at mRNA levels after knockdown of FACT in our present study, our data support the notion that FACT exerts its influence on p27 at post-transcriptional levels. The reduction in both mRNA and protein levels of SKP2 and c-MYC with knockdown of FACT and an enrichment of FACT binding at c-MYC promoter region indicate that FACT enhances the transcription of c-MYC in prostate and lung cancer cells.…”
Section: Discussionsupporting
confidence: 88%
“…c‐MYC can repress p27 but induce SKP2 gene transcription . Accordingly, c‐MYC, SKP2, and p27 have been proposed to form a network, and reducing the activity of c‐MYC and SKP2 or boosting nuclear p27 expression is explored as a therapeutic strategy . Since p27 was increased at only protein levels but not at mRNA levels after knockdown of FACT in our present study, our data support the notion that FACT exerts its influence on p27 at post‐transcriptional levels.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that EYA4 was upregulated in glioma and its levels were positively correlated with advanced tumor stage, which was consistent with its previously reported roles in other cancers. The cyclin kinase inhibitor p27Kip1 is considered as a tumor suppressor that plays a critical role in cell proliferation, differentiation, and apoptosis [35][36][37][38]. Dysregulation of p27Kip1 gene expression at the mRNA or the protein level was reported in various cancers [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the G1 to S phases of the cell cycle, the E3 ligase SKP2 can interact with c-Myc and mediate its degradation by ubiquitination, thereby blocking the cell cycle and inhibiting tumorigenesis. 205,206 Additionally, the phosphorylation of c-Myc on Thr58 by GSK3 promotes its interaction with Fbw7 and facilitates K48 linkage polyubiquitination. The subsequent degradation inhibits cell proliferation and tumor growth.…”
Section: Ubiquitination In Tumor Metabolism Regulationmentioning
confidence: 99%